2022
DOI: 10.35377/saucis...1084024
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Recent Developments on Secure Authentication Using RF Fingerprints Techniques

Abstract: The Internet of Things (IoT) concept is widely used today. As IoT becomes more widely adopted, the number of devices communicating wirelessly (using various communication standards) grows. Due to resource constraints, customized security measures are not possible on IoT devices. As a result, security is becoming increasingly important in IoT. It is proposed in this study to use the physical layer properties of wireless signals as an effective method of increasing IoT security. According to the literature, radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…It has been shown that every transmitter has a distinct RF fingerprint, and it is also demonstrated how unlikely it is for two transmitters to share the same RF features. Accordingly, such a unique RF fingerprint can be used to authenticate the identity of a particular wireless transmitter and guarantee the confidentiality of the messages that are sent [48,49].…”
Section: Radio Frequency Fingerprintingmentioning
confidence: 99%
“…It has been shown that every transmitter has a distinct RF fingerprint, and it is also demonstrated how unlikely it is for two transmitters to share the same RF features. Accordingly, such a unique RF fingerprint can be used to authenticate the identity of a particular wireless transmitter and guarantee the confidentiality of the messages that are sent [48,49].…”
Section: Radio Frequency Fingerprintingmentioning
confidence: 99%
“…Our survey differs from those presented by the authors of [93][94][95][96] that use IoT as motivation or context for their surveys but do not use IoT as a lens through which to analyze the surveyed SEI papers, as we do herein. This survey aims to answer: "What technical gaps must be addressed for SEI to be a viable PLS solution for IoT deployments?"…”
Section: Surveymentioning
confidence: 99%
“…The resulting fingerprint features (feature vector) for each burst consist of 24D features (2 types of data × 2 types of features × 4 statistical features). The fingerprint features from device c can be given by Equation (30).…”
Section: Iet Signal Processingmentioning
confidence: 99%
“…Other features, such as constellation trajectory mapping features [22,23], fractal dimensional features [24,25], and multidimensional integrated features, have also been studied more [26][27][28]. For databased intelligent processing methods, deep models are used for automatic feature extraction and individual classification and recognition [29][30][31][32][33][34]. However, the models used are becoming increasingly complex and require very large data samples to train, which are not suitable for application to micromodels or microsystems.…”
Section: Introductionmentioning
confidence: 99%